An Update on the Potential Application of Herbal Medicine in Promoting Angiogenesis - Jingjing Li; Renkai Li; Xiaoping Wu; Chengwen Zheng; Polly Ho-Ting Shiu; Panthakarn Rangsinth; Simon Ming-Yuen Lee; George Pak-Heng Leung (Frontiers Media S.A., 2022)
Angiogenesis, the formation of new capillaries from pre-existing vascular networks, plays an important role in many physiological and pathological processes. The use of pro-angiogenic agents has been proposed as an attractive approach for promoting wound healing and treating vascular insufficiency-related problems, such as ischemic heart disease and stroke, which are the leading causes of death worldwide. Traditional herbal medicine has a long history; however, there is still a need for more in-depth studies and evidence-based confirmation from controlled and validated trials. Many in vitro and in vivo studies have reported that herbal medicines and their bioactive ingredients exert pro-angiogenic activity. The most frequently studied pro-angiogenic phytochemicals include ginsenosides from Panax notoginseng, astragalosides and calycosin from Radix Astragali, salvianolic acid B from Salvia miltiorrhiza, paeoniflorin from Radix Paeoniae, ilexsaponin A1 from Ilex pubescens, ferulic acid from Angelica sinensis, and puerarin from Radix puerariae. This review summarizes the progress in research on these phytochemicals, particularly those related to pro-angiogenic mechanisms and applications in ischemic diseases, tissue repair, and wound healing. In addition, an outline of their limitations and challenges during drug development is presented.